Leveraging the dynamic adaptation process to address LGBTQ+ health equity in New Mexico high schools - Willging, Cathleen Elizabeth; Shattuck, Daniel; Ramos, Mary M.; Richard, Bonnie O.; Lawyer, Adrien; Dickson, Elizabeth; Aarons, Gregory A. (Frontiers in Health Services, 2025)
BackgroundReducing adolescent suicide in the United States is a public health priority, and lesbian, gay, bisexual, transgender, and queer (LGBTQ+) youth are at elevated risk. The Centers for Disease Control and Prevention has identified six evidence-informed school-based practices (EIPs) that enhance health equity and potentially reduce suicide-related behavior for LGBTQ+ students. Guided by the Exploration, Preparation, Implementation, Sustainment (EPIS) framework, we conducted a five-year, community-engaged cluster randomized controlled trial in 42 New Mexican high schools to study the implementation of these six EIPs. This paper assesses the effectiveness, utility, and benefits of the study's implementation strategy—the Dynamic Adaptation Process (DAP), a participatory and multifaceted implementation approach.MethodsOur convergent parallel mixed-method analysis focused on 22 New Mexico high schools randomized into an implementation condition. Data sources included annual structured assessments of EIP implementation, individual and small-group qualitative interviews with school professionals, periodic debriefs and interviews with implementation coaches, and coach activity logs. We analyzed quantitative data using linear regressions and qualitative data using deductive coding techniques, integrating the results through a joint display.ResultsThe schools experienced statistically significant changes compared to their baseline in adopting safe spaces, prohibitions on bullying and harassment based on LGBTQ+ identity, inclusive health education materials, staff professional development, and facilitation of students' access to LGBTQ+ affirming healthcare. We attribute these changes to the impact of the DAP. The DAP facilitated collaboration among school professionals and community organizations to shift knowledge and attitudes and execute contextually responsive implementation strategies. It also fostered relationship-building and leadership, encouraging school leaders to legitimate implementation efforts and champion health equity for LGBTQ+ students.DiscussionParticipatory implementation science models like the DAP can help prioritize health equity for marginalized populations by enabling the uptake of practices likely to contribute to well-being. This mixed-methods study provides a rich example for future research tackling health disparities for LGBTQ+ people in schools and other complex systems.